2013
DOI: 10.18227/1982-8470ragro.v6i3.705
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho da mucuna preta (Mucuna aterrima Piper & Tracy) na fitorremdiação de solo contaminado com chumbo

Abstract: Resumo -. Os tratamentos foram distribuídos no delineamento inteiramente casualizado com três repetições. Amostras do solo e do tecido vegetal foram coletadas noventa dias após a semeadura para a quantificação das massas das matérias secas da parte aérea e das raízes para a determinação do acúmulo de chumbo. Os dados obtidos foram submetidos à análise de variância e regressão. As plantas de mucuna preta apresentaram maior acúmulo de Pb em sua parte aérea, em função da massa de matéria seca produzida; não houve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
2
1
1
Order By: Relevance
“…The Pb concentration was lowest in forage peanut roots showing a significant increase in Pb translocation to the leaves (Figure 3). This finding is contrary to those reported by Santos et al (2012) and Romeh et al (2016) who reported higher amounts of lead in roots than in shoots.…”
Section: Shoot Dry Matter (Sm) and Root Dry Matter (Rm)contrasting
confidence: 99%
See 2 more Smart Citations
“…The Pb concentration was lowest in forage peanut roots showing a significant increase in Pb translocation to the leaves (Figure 3). This finding is contrary to those reported by Santos et al (2012) and Romeh et al (2016) who reported higher amounts of lead in roots than in shoots.…”
Section: Shoot Dry Matter (Sm) and Root Dry Matter (Rm)contrasting
confidence: 99%
“…However, Pb rates linearly reduced the root dry matter (Figure 2). Reductions of dry matter production in many plant species as a function of doses of Pb in experiments with soil and nutrient solution were reported by other authors (Paiva et al, 2002;Sharma and Dubey, 2005;Lindino et al, 2012;Santos et al, 2012;Redovniković et al, 2017). In the current study the lead rates did not influence shoot dry matter production, which was similarly reported by Lindino et al (2012) for Crotalaria spectabilis.…”
Section: Shoot Dry Matter (Sm) and Root Dry Matter (Rm)supporting
confidence: 89%
See 1 more Smart Citation
“…Nesse caso, a utilização de plantas remediadoras surge como alternativa para acelerar a degradação dos herbicidas. Várias pesquisas, tanto no Brasil quanto no exterior, têm demonstrado a efeciência dessa técnica em diversos ecossistemas contaminados com compostos orgânicos e inorgânicos (MADALÃO et al, 2012a, b;SANTOS et al, 2012;MITTER et al, 2013;OLIVEIRA et al, 2014;MITTON et al, 2014).…”
Section: Introductionunclassified
“…In fact, several research works have been performed on plant species used as possible lead phytoremediation, such as: Pistia stratiotes (OLIVEIRA, 2010), Leucaena leucocephala (BOURLEGAT et al, 2008), Eichhornia crassipes (PEREIRA, 2010;OLIVEIRA et al, 2014), Stizolobium aterrimum , Pluchea sagittalis (ROSSATO, 2010), Ricinus communis (LIMA, 2010b), Helianthus annuus (LIMA, 2010), Canavalia ensiformis (ROMEIRO et al, 2007), Mucuna aterrima (SANTOS et al, 2012), Jatropha curcas (GOUVEIA et al, 2015), Salvinia auriculata (ALMEIDA, 2014). (PEREIRA, 2010), and the metal accumulation in the aerial part of the plant .…”
Section: Lead Remediation In the Environmentmentioning
confidence: 99%